Perbandingan Life Skill Antara Model Pembelajaran CTL, Jigsaw Memperhatikan Konsep Diri Siswa - Serginia Zenda; Nurdin Nurdin; Yon Rizal (FKIP Unila, 2018)
The purpose of this study is to find comparison life skill between learning modelCTL, jigsaw see the concept of self public smp students 7 kotabumi. Methodsused in this research is kompratif with the approach experiment .This populationwere 240 students .Sample obtained 60 students .The results of the analysis of thedata shows (1) no difference in life skill lesson that students use learning modelCTL (Contextual Teaching and Learning) than using a model learning Jigsaw (2)Student Life Skill lesson using the learning model of CTL (Contextual Teachingand Learning) is better than using a Jigsaw in students who have a positive selfconcept. (3) Life Skill lesson that students use Jigsaw learning model is betterthan using the CTL (Contextual Teaching and Learning) on students who havenegative self concept. (4) there are interactions between the learning model withself concept of students against Life Skill subjects Integrated IPS.Tujuan dari penelitian ini adalah untuk mengetahui Perbandingan Life Skill AntaraModel Pembelajaran CTL, Jigsaw Memperhatikan Konsep Diri Siswa SMPNegeri 7 Kotabumi. Metode yang digunakan dalam penelitian ini adalahkompratif dengan pendekatan eksperimen. Populasi ini berjumlah 240 siswa.Sampel yang diperoleh 60 siswa.Hasil analisis data menunjukkan (1) Adaperbedaan life skill siswa yang pembelajarannya menggunakan modelpembelajaran CTL (Contextual Teaching and Learning) dibandingkanmenggunakan model pembelajaran Jigsaw (2) Life Skill siswa yangpembelajarannya menggunakan model pembelajaran CTL (Contextual Teachingand Learning) lebih baik dibandingkan menggunakan Jigsaw pada siswa yangmemiliki konsep diri yang positif. (3) Life Skill Siswa yang pembelajarannyamenggunakan model pembelajaran Jigsaw lebih baik dibandingkan menggunakanCTL (Contextual Teaching and Learning) pada siswa yang memiliki konsep diriyang negatif. (4) Ada interaksi antara model pembelajaran dengan konsep dirisiswa terhadap Life Skill pada mata pelajaran IPS Terpadu.Kata kunci: life skill, konsep diri, CTL, jigsaw